Influencia de los o-lan sic en la educación ambiental de estudiantes de educación de la universidad nacional toribio rodríguez de mendoza de amazonas, 2011 - Lázaro Bazán, Ever Salomé (2012)
The investigation verified the development of the Organizers Logical Analytical and Synthetic Creative (O-LAN-SIC) significantly influencing the environmental education of the students of the Faculty Education of the University National Toribio Rodríguez of Mendoza of Amazonas (UNTRM-A). Working with 27 students, as Experimental Group and 27 as a control group. A test was used on the O-LAN-SIC and environmental education, to measure the level of influence of the O-LAN-SIC in environmental education through the scale: excellent, good, regular and bad. To apply the pre and post test to both groups was obtained the following results: In the pre-test of the experimental group, 20 (74 %) achieved a level of influence and 7 regular (26 %) obtained the bad level. In the control group, 18 (67 %) obtained the regular level and 9 (33 %) the bad level. In the post test of the experimental group the 37% achieved the excellent level, the 52% level the good, the 11% regular and bad was reduced to 0 %. The development of the O-LAN-SIC and the workshops on environmental education with the experimental group were executed in three months: 12 sessions and 28 activities. Then the pos test was applied to both groups, checking is that the development of the O-LAN-SIC influence significantly in the Environmental education of the students of the Faculty of Education of the National University Toribio Rodríguez of Mendoza of the Amazonas.